2017
DOI: 10.1007/s10695-017-0354-3
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory role of L-carnitine against microcystin-LR-induced immunotoxicity and oxidative stress in common carp

Abstract: Microcystin-LR (MCLR), one of the most popular microcystins (MCs) found in many field water bodies around the world, poses great health risks to animals and humans. In the present study, healthy common carp (initial weight 24.8 ± 2.3 g) were randomly assigned to five groups. Group I was fed on normal diet as control. Group II was maintained on normal diet and received MCLR intraperitoneal injection (150 μg kg BW). Common carp in groups III, IV, and V were daily pretreated with L-carnitine (LC) at doses of 0.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…It is postulated that proinflammatory cytokines production could be induced by oxidative stress which was caused by fish oil (Naik and Dixit, 2011), and the lipid peroxidation could be the main reason of the oxidative stress. Similar results were also found in common carp (Cyprinus carpio) (Chen X. M. et al, 2017), large yellow croaker (Larmichthys crocea) , and rat (Rattus norvegicus) (Sanders et al, 2004). Additionally, considerable research supports that n-3 PUFA can induce lipid peroxidation (Pupe et al, 2002;Muralidhar et al, 2004).…”
Section: Discussionsupporting
confidence: 69%
“…It is postulated that proinflammatory cytokines production could be induced by oxidative stress which was caused by fish oil (Naik and Dixit, 2011), and the lipid peroxidation could be the main reason of the oxidative stress. Similar results were also found in common carp (Cyprinus carpio) (Chen X. M. et al, 2017), large yellow croaker (Larmichthys crocea) , and rat (Rattus norvegicus) (Sanders et al, 2004). Additionally, considerable research supports that n-3 PUFA can induce lipid peroxidation (Pupe et al, 2002;Muralidhar et al, 2004).…”
Section: Discussionsupporting
confidence: 69%
“…The mRNA expression of anti-inflammatory genes (il-10 and arg-1) was increased in fish fed the diet with the 75 % TOC compared with 75 % TO. Previous studies have demonstrated that dietary L-carnitine can improve the immunity and disease resistance of juvenile narrow clawed crayfish (Astacus leptodactylus leptodactylus) (66) , black carp (Mylopharyngodon piceus) (67) and common carp (Cyprinus carpio L.) (68) . L-Carnitine exerted protective effects by inhibiting the generation of ammonia and xenobiotics in rat hepatocytes (69) .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the liver, the testis is another target organ for MC-LR; its presence not only disrupts motility and morphology of sperm but also alters male hormone levels (Lone et al 2015;Zhang et al 2017a). Moreover, immunotoxicity (Chen et al 2017), genotoxicity (Zegura 2016), and developmental toxicity (Qi et al 2016) associated with this cyanotoxin has been investigated.…”
Section: Introductionmentioning
confidence: 99%